A quasi three dimensional numerical model for terrain propagation - Bradley, Ronan (Trinity College (Dublin, Ireland). Department of Electronic & Electrical Engineering, 2002)
Numerical modeling techniques provide a powerful tool for the optimization of modern land mobile radio communications systems. Mathematically, propagation over terrain constitutes a three-dimensional vector field problem . However, the majority of conventional numerical modeling techniques make use of a two dimensional terrain approximation, leading to a scalar field representation, and as a consequence, make no allowance for depolarization phenomena.
Keywords: Electronic and Electrical Engineering, Ph.D.; Ph.D. Trinity College Dublin